Concave and duck web-like platinum nanopentagons with enhanced electrocatalytic properties for formic acid oxidation. Issue 3 (17th December 2015) - Lai, Jianping; Niu, Wenxin; Li, Suping; Wu, Fengxia; Luque, Rafael; Xu, Guobao
Abstract : Pt-branched structures featuring concave and duck web-like nanopentagons with high-energy 110 and 554 facets, multiple twin boundaries, duck web-like edges and inherent anisotropic branches are prepared. Abstract : Pt-branched structures featuring concave and duck web-like nanopentagons (CWPNP), with surfaces enclosed by 111 facets, high-energy 110 and 554 facets, multiple twin boundaries, duck web-like edges and inherent anisotropic branches are herein reported. The unique chemisorption properties and reducing capacities of tri- n -propylamine and oleylamine, as well as the inhibition of oxidative etching of the twin defects by the exclusion of chloride ions contribute to the formation of Pt CWPNP. Pt CWPNP exhibited unprecedented electrocatalytic activities, high antipoisoning activity and durability in formic acid oxidation reaction (FOR) in comparison to commercial Pt/C and Pt black, and thus is a promising catalyst for the FOR. The excellent FOR performance of Pt CWPNP is attributed to the least poisoned 111 facets, active sites by high-energy facets, multiple twin boundaries, duck web-like edges and inherent anisotropic branches composed of 1D nanowires. It is anticipated that this study will offer a new approach for the design of surface structure-controlled FOR electrocatalysts.